EP400 Feasibility of FDG-PET-MRI during chemo-radiotherapy for cervical cancer. (1st November 2019) - Sarwar, A; Narayanan, P; Kiyani, I; Eminowicz, G
Abstract : Introduction/Background: Curative treatment for locally advanced cervical cancer is chemo-radiotherapy and intrauterine brachytherapy. Early identification of patients who are not responding adequately allows treatment adaptation. This has the potential to improve overall survival, spare unnecessary side-effects and reduce healthcare costs associated with ineffective treatment. Diffusion-weighted magnetic resonance imaging (DW-MRI) and fluorodeoxyglucose-positron emission tomography (FDG-PET) may be used to enhance assessment of response during and after chemo-radiotherapy allowing prompt treatment adaptation. Methodology: A feasibility non randomised cohort study of PET-MRI is currently recruiting cervical cancer patients having definitive chemo-radiotherapy. PET-MRI imaging is added to the standard of care at baseline and week 5 of treatment. A patient experience questionnaire is completed at baseline and week 5. Apparent diffusion coefficient (ADC) for DW-MRI and standardised uptake values (SUV) for PET-MRI were derived, comparing baseline to week 5 and within each scan to investigate the distribution of imaging parameters obtained from areas of responding, progressing and stable disease. Results: Six patients have been recruited. Two patients did not undergo week 5 imaging. All patients found the imaging attendances acceptable. All patients had a significant reduction in SUVmax in week 5 compared to pre-treatment. All patients had an increase in ADC during treatment which was significant for patient 2 & 3. A significant correlation was seen in reduction of SUVmax and increase in ADC, r=0.98, p value=0.0172 (95% CI 0.39–0.0.99). Conclusion: Early data suggests additional imaging to obtain biological data during chemo-radiotherapy is feasible with no detrimental impact on patient experience. Identification of a non-responding 'biological target volume' using ADC and SUVmax parameters could allow personalisation of brachytherapy, delivering a high dose boost to residual disease. This study identifies the feasibility of PET-MRI as an imaging biomarker. Disclosure: Nothing to disclose.